Aspectos ecológicos de la nutria neotropical (Lontra longicaudis annectens) en el camino La Veleta en la Laguna de Términos, Campeche, México - Santiago-Plata, Víctor Manuel; Valdez-Leal, Juan Dios; Pacheco-Figueroa, Coral Jazvel; de la Cruz-Burelo, Fabiola; Moguel-OrdónÌƒez, Eduardo Javier (THERYA, 2013)
We studied some ecological aspects of the neotropical Otter on the La Veleta dirt road located in the intensive use area of the Flora and Fauna Protection Area (Área de Protección de Flora y Fauna) â€œLaguna de Terminosâ€. We conducted this study from March to December of 2007, it consisted on the search and identification of otter traces in a dirt road and channels in the zone. A total of 120 km were covered, and 104 traces were found (35 tracks, 16 sunning places, 29 scats, 16 latrines and 8 direct observations). We estimated a mean relative abundance of 0.86 Â± 0.472 tracks/km. Temporarily the highest abundance was obtained during the Northern winds season (1.12 Â± 0.288 tracks/km) and the lowest abundance was recorded during the dry season (0.70 Â± 0.242 tracks/km). In addition to the 29 stools collected along the transects, we collected another 77 in nearby areas for a total of 106 stools. Fish (54.7%) was the highest consumption group, followed by crustaceans (20.5%), mollusks (14.8%), reptiles (5.1%) and insects (4.9%). No significant differences were found in the frequency of consumption of prey groups per season (X2 = 5267, df = 4, P < 0.261). Results suggest that otters are permanently in the area and that environmental changes on the area, exerts some influence in their abundance, diet and seasonal movements. It is recommended that the vegetation cover in the study area are protected, and the prevention of pollution in the water bodies. Key words: abundance, diet, distribution, neotropical otter, Laguna de Términos.